Quantitative fluorescence-based imaging of in-cylinder fuel film thickness at kHz frame rates in a production-type direct-injection spark-ignition engine. (June 2023) - Schöler, Jonathan; Wigger, Stefan; Kaiser, Sebastian A
Incomplete evaporation of liquid fuel films inside the combustion chamber is a major source of soot and particulate emissions in internal combustion engines. In this study, quantitative imaging of liquid fuel films on the cylinder wall is performed by laser-induced fluorescence (LIF) in a single cylinder engine with optical access to the cylinder liner. A four-component surrogate fuel mixed with 0.5% anisole as the fluorescent tracer was directly injected in a single injection into the motored engine. Fuel impinging on the cylinder wall is excited at 266 nm at kHz repetition rates and imaged by a high-speed camera coupled with an image intensifier. Simultaneously, lubricating oil doped with 0.01 mmol/l pyrromethene 567 is excited at 532 nm and imaged with a second camera. The fuel film thickness on the cylinder wall is compared for two different injections timings, 285 and 240°CA before top-dead center. The initial fuel film thickness is similar for both, but evaporation occurs faster for the later injection, such that the film thickness is similar at the time the piston rings reach the fuel films. When the rings scrape the fuel off the wall, it accumulates on top of the first piston ring and is partly transported downwards to the second and third ring. In the simultaneous oil image, washout of lubricating oil is seen.